2006
DOI: 10.1074/jbc.m513314200
|View full text |Cite
|
Sign up to set email alerts
|

Shielding of the A1 Domain by the D′D3 Domains of von Willebrand Factor Modulates Its Interaction with Platelet Glycoprotein Ib-IX-V

Abstract: Soluble von Willebrand factor (VWF) has a low affinity for platelet glycoprotein (GP) Ib␣ and needs immobilization and/or high shear stress to enable binding of its A1 domain to the receptor. The previously described anti-VWF monoclonal antibody 1C1E7 enhances VWF/GPIb␣ binding and recognizes an epitope in the amino acids 764 -1035 region in the N-terminal DD3 domains. In this study we demonstrated that the DD3 region negatively modulates the VWF/GPIb-IX-V interaction; (i) deletion of the DD3 region in VWF aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 41 publications
6
107
0
2
Order By: Relevance
“…The DЈA3 fragment was chosen because it does not form multimers; therefore, it can be used for kinetic studies in which spatial separation of the A1 domains is essential, while still encompassing the OLGs and structural elements that have been suggested to influence accessibility of the A1 domain. 31,32 We first confirmed that all the DЈA3 mutants bound to the flow slides to a similar extent as wtDЈA3. Immobilized proteins were recovered from the slides and analyzed by SDS-PAGE followed by Western blotting and immunostaining with both polyclonal anti-VWF antibody ( Figure 2C) and anti-c-myc tag antibodies ( Figure 2D).…”
Section: Vwf Olgs Modulate Platelet Translocation Over Vwfsupporting
confidence: 67%
“…The DЈA3 fragment was chosen because it does not form multimers; therefore, it can be used for kinetic studies in which spatial separation of the A1 domains is essential, while still encompassing the OLGs and structural elements that have been suggested to influence accessibility of the A1 domain. 31,32 We first confirmed that all the DЈA3 mutants bound to the flow slides to a similar extent as wtDЈA3. Immobilized proteins were recovered from the slides and analyzed by SDS-PAGE followed by Western blotting and immunostaining with both polyclonal anti-VWF antibody ( Figure 2C) and anti-c-myc tag antibodies ( Figure 2D).…”
Section: Vwf Olgs Modulate Platelet Translocation Over Vwfsupporting
confidence: 67%
“…The primary structure of the mature vWF protein describes the A1 domain as being flanked by the DЈD3 domains in the N-terminal region, and those domains have been described to be involved in the mechanism that inhibits the vWF-GPIb␣ interaction by shielding the A1 domain (22). However, the binding site for GPIb␣ in the A1 domain remained cryptic in our A1A2A3 protein, which excludes the DЈD3 domains (4).…”
mentioning
confidence: 61%
“…These contacts may allow the D3 and/or other domains to regulate the forced dissociation of A1 from GPIbα in a manner similar to that of the salt bridges between D1269 and R1306/R1450. This may explain why deleting the D′D3 region augments binding to GPIbα and adding an isolated D′D3 region inhibits GPIbα binding to vWF lacking this region (48). Deleting the D′D3 region (residues 764-1259) may affect the D1269:R1306/R1450 salt bridges, causing a gain-of-function phenotype like that of R1450E A1.…”
Section: Figurementioning
confidence: 99%